Building a Research Ecosystem Based on Collaboration among ELT Students for Sustainable Technological Innovation - Ega Nur Fadillah; Nuha Nabila Huda (PT. Publikasiku Academic Solution, 2025)
This research aimed to formulate a research ecosystem model based on collaboration among ELT students that can foster innovation in the field of sustainable technology. Using a qualitative-descriptive approach, data were collected through literature studies, surveys, and in-depth interviews with students and education experts. The results showed that a collaborative research ecosystem involving ELT students across disciplines and institutions can enhance students’ innovation capacity and research skills while strengthening local technological competitiveness. Constraints in the development of this ecosystem include limited infrastructure support and resources, which can be addressed through educational policies that promote inter-campus collaboration and improve research facilities. This study concluded that building a research ecosystem based on ELT student collaboration is an effective strategy for fostering sustainable technological innovation and provides recommendations for universities and the government to facilitate the creation of an ecosystem that supports research collaboration. The findings imply that institutional commitment and cross-disciplinary synergy are crucial for translating student-led research into impactful, real-world sustainable solutions.